Sharps injuries prevention among healthcare providers in surgical, medical and pediatric wards of a public hospital in Jimma Zone: a best practice implementation project. Issue 3 (5th September 2021) - Asefa, Yisalemush; Admassu, Bitiya; Wondimnew, Tesaka; Morankar, Sudhakar
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Sharps injuries are a serious public health problem that healthcare providers face and constitute a major risk for the transmission of blood-borne infections. Prevention of sharps injuries in hospitals requires that healthcare providers comply with universal precautions. Objectives: The aim of this study was to assess and improve the compliance of healthcare providers with protocols based on best available evidence for prevention of sharps injuries in medical, surgical and pediatric wards of the hospital. Methods: A three-phase clinical audit was carried out using the online JBI Practical Application of Clinical Evidence System and Getting Research into Practice Program. Six audit criteria based on available evidence were used. Phase 1 of the project was the baseline audit, phase 2 the implementation of the best practice, and phase 3 the follow-up audit. Data were collected through observation, interview and resource inventory. Results: The postintervention compliance report showed maximum improvement in compliance in criterion 1 (sharps containers are not filled above the mark that indicates the bin is full) and criterion 2 (sharps containers are positioned out of the reach of children at a height that enables safe disposal by staff). Between the baseline and postintervention audits, the compliance rate for these criteria improved by more than half (criterion 1) and by nine-fold (criterion 2) (from 38 to 100% and 0 to 93%, respectively). During baseline, two nurses reported experiencing sharps injuries, noting that they think it is not important to report the injury if the patient is negative for HIV, and when they do not know where to report it, regardless. At the postintervention audit no injuries were reported. Conclusion: The best practice recommendations using a clinical audit process was an effective intervention for improving knowledge and compliance of healthcare workers with protocols for the prevention of sharps injuries in low-resource settings.